A girl with incomplete Prader–Willi syndrome and negative MS‐PCR, found to have mosaic maternal UPD‐15 at SNP array. (24th June 2015) - Morandi, Anita; Bonnefond, Amélie; Lobbens, Stéphane; Carotenuto, Marco; del Giudice, Emanuele Miraglia; Froguel, Philippe; Maffeis, Claudio
<x xml:space="preserve">Abstract</x> The Prader–Willi syndrome (PWS) is caused by lack of expression of paternal allele of the 15q11.2‐q13 region, due to deletions at paternal 15q11.2‐q13 (<70%), maternal uniparental disomy of chromosome 15 (mat‐UPD 15) (30%) or imprinting defects (1%). Hyperphagia, intellectual disabilities/behavioral disorders, neonatal hypotonia, and hypogonadism are cardinal features for PWS. Methylation sensitive PCR (MS‐PCR) of the SNRPN locus, which assesses the presence of both the unmethylated (paternal) and the methylated (maternal) allele of 15q11.2‐q13, is considered a sensitive reference technique for PWS diagnosis regardless of genetic subtype. We describe a 17‐year‐old girl with severe obesity, short stature, and intellectual disability, without hypogonadism and history of neonatal hypotonia, who was suspected to have an incomplete PWS. The MS‐PCR showed a normal pattern with similar maternal and paternal electrophoretic bands. Afterwards, a SNP array showed the presence of iso‐UPD 15, that is, UPD15 with two copies of the same chromosome 15, in about 50% of cells, suggesting a diagnosis of partial PWS due to mosaic maternal iso‐UPD15 arisen as rescue of a post‐fertilization error. A quantitative methylation analysis confirmed the presence of mosaic UPD15 in about 50% of cells. We propose that complete clinical criteria for PWS and MS‐PCR should not be considered sensitive in suspecting and diagnosing partial PWS due to mosaic UPD15. In contrast, clinical suspicion based on less restrictive criteria followed by SNP array is a more powerful approach to diagnose atypical PWS due to UPD15 mosaicism. © 2015 Wiley Periodicals, Inc.